Pengaruh Sistem Pengendalian Internal Piutang Terhadap Efektivitas Pengelolaan Piutang Pada Dana Amanah Pemberdayaan Masyarakat Unit Pengelola Kegiatan (Upk) Kecamatan Watang Sidenreng - Yunus, Rahayu; Kurniawan, Kurniawan; Yahya, Yahya (Paser Institute Of Accounting and Finance, 2025)
This study aims to determine how much influence the internal control system of receivables has on the Effectiveness of Receivables Management in Community Empowerment Trust Fund UPK of Watang Sidenreng District, the type of research used in this study is Quantitative with a survey method, the sample in this study was 64 respondents, Data collection techniques conducted observations and distributed questionnaires to respondents then the analysis method used was Multiple Regression. The results of the study indicate that the variables of the Internal Control System of Receivables together or simultaneously have an influence on the Effectiveness of Receivables Management, the significant value obtained is 0.000, much smaller than 0.05. The Control Environment (X1) does not affect the Effectiveness of Receivables Management with a significance value obtained of 0.472, greater than 0.05. Control Activities (X2) partially have a positive and significant effect on the Effectiveness of Receivables Management with a significance value of 0.019, which is smaller than 0.05., Risk Assessment (X3) does not affect the Effectiveness of Receivables Management with a significance value of 0.521, which is greater than 0.05., Information and Communication (X4) partially have a positive and significant effect on the Effectiveness of Receivables Management with a significance value of 0.031, which is smaller than 0.05., Monitoring (X5) partially has a positive and significant effect on the Effectiveness of Receivables Management with a significance value of 0.000, which is smaller than 0.05.